STRATEGI PENGEMBANGAN PELABUHAN PERIKANAN NIZAM ZACHMAN DALAM MENDUKUNG INDUSTRI PERIKANAN TUNA - Roma Yuli Felina Hutapea; Iin Solihin; Tri Wiji Nurani; Ayang Armelita Rosalia; Aprilia Syah Putri (Jurnal Teknologi Perikanan dan Kelautan, 2019)
The role of fishing ports required in tuna fishing industries. Oceanic Fishing Port Nizam Zachman is a tuna fishing port in Indonesia, which includes the tuna fishing industrty. The increasing role of Nizam Zachman Oceanic Fishing Port is needed by tuna stakeholders to optimize the performance and services provided by the port. The aimed of the research was to formulate the development strategy of tuna industries, which is competitive with used the role of Nizam Zachman Oceanic Fishing Port. The analysis methods that used in this research was SWOT analysis by comparing the internal factors and external factors tuna fisheries development. The results showed that there were 6 tuna fisheries development strategy by optimizing the role of Nizam Zachman Oceanic Fishing Port.